The Effectiveness of Bluey Cartoon Series as And Educational Medium for Developing Communicative Competence at SD IT Imam Syafe'i Pekanbaru - Oktadela, Resy; Elida, Yusti; Hadiyanti, Putri Octa; Roziah, Roziah; Ismail, Syofianis; Maulana, Rezky (Journal of English Language and Education, 2025)
This research investigated the effects of Bluey cartoon integration on primary school students' oral communication and aural comprehension competencies, as well as their perceptions of Bluey cartoon based pedagogical approaches in English language instruction in SD IT Imam Syafei’ Pekanbaru. An experimental methodology was adopted for data collection purposes. The participant pool comprised 19 fourth-grade students allocated into control and experimental cohorts. The control cohort received conventional English instruction, whereas the experimental cohort engaged with comparable curricular content supplemented with cartoon-based activities targeting oral and aural skill development over a six-week intervention period. Pre-intervention and post-intervention assessments were administered to both cohorts to evaluate their speaking and listening proficiencies. Furthermore, a questionnaire was distributed to the experimental cohort to ascertain their perceptions regarding the pedagogical utilization of Bluey cartoons. Results indicated that students in the experimental cohort demonstrated statistically significant improvements in English speaking and listening competencies relative to their counterparts in the control cohort. Additionally, experimental cohort participants exhibited favorable attitudes toward cartoon integration in English language instruction. These findings hold pedagogical implications for English language educators in SD IT Imam Syafei ‘ Pekanbaru and comparable contexts where English functions as a foreign language, suggesting the incorporation of visual instructional materials to facilitate young learners' linguistic development.